Can Belief in a Just World Buffer Mood and Career Prospects of People in Need of Risk Protection? First Experimental Evidence. Issue 12 (18th February 2016) - Nudelman, Gabriel; Otto, Kathleen; Dalbert, Claudia
Abstract : Research indicates that individuals high in belief in a just world (BJW) are confident that they will not fall victim to unforeseeable disasters. The current study tested the hypothesis that BJW acts as buffer that serves to sustain mood and career prospects of those in need of risk protection. Threat was manipulated by confronting participants with risks regarding their career outlook, and individual differences in threat perception were measured by degree of uncertainty tolerance. As hypothesized, BJW helped protect the mood of participants threatened by serious career‐related risks who were unable to tolerate uncertainty. The finding supported the buffer hypothesis regarding mood, but not career prospects, possibly due to a more conscious mindset or variability in self‐efficacy. However, BJW was overall positively associated with career prospects. Moreover, it was suggested that BJW can also serve as a personal resource, not only protecting from risk, but also enhancing mood among those with high uncertainty tolerance.